2021
DOI: 10.1080/21655979.2021.2002497
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long non-coding RNA-microRNA-mRNA competing endogenous RNAregulatory networks in thromboangiitis obliterans

Abstract: Thromboangiitis obliterans (TAO) is a non-atherosclerotic, segmental, chronic vascular inflammatory disease. Our aim was to explore the underlying mechanisms of long non-coding RNA (lncRNA)-related competing endogenous RNAs (ceRNAs) in TAO. Six blood samples were collected from patients with TAO and healthy individuals (three for each category). Total RNA was extracted from the blood of each participant and sequenced. Differentially expressed lncRNAs (DE-lncRNAs) and miRNAs (DE-miRNAs) were screened, and ceRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Notably, exosomal miR-3124-5p was selected as a key player in CHOL development based on our experimental validations. A previous study has revealed that the level of miR-3124-5p in patients with thromboangiitis obliterans is significantly higher than that in healthy individuals ( 35 ), suggesting the potential role of miR-3124-5p in thromboangiitis obliterans. Moreover, miR-3124-5p has been shown to be associated with multiple cancers, such as gastric cardia adenocarcinoma ( 36 ) and triple-negative breast cancer ( 37 ).…”
Section: Discussionmentioning
confidence: 92%
“…Notably, exosomal miR-3124-5p was selected as a key player in CHOL development based on our experimental validations. A previous study has revealed that the level of miR-3124-5p in patients with thromboangiitis obliterans is significantly higher than that in healthy individuals ( 35 ), suggesting the potential role of miR-3124-5p in thromboangiitis obliterans. Moreover, miR-3124-5p has been shown to be associated with multiple cancers, such as gastric cardia adenocarcinoma ( 36 ) and triple-negative breast cancer ( 37 ).…”
Section: Discussionmentioning
confidence: 92%
“…The interaction of non-coding RNAs, especially lncRNAs and miRNAs, forms a complex regulatory network and participates in the occurrence and development of many diseases [ 75 ]. Studies have reported that the lncRNA–miRNA–mRNA axis plays an important role in vascular diseases [ 76 , 77 ]. Animal experiments have shown that knockout of lncRNA ANRIL reduces thrombosis in rats [ 78 ].…”
Section: Regulatory Effects Of Non-coding Rnas Of Epcs Involved In Ve...mentioning
confidence: 99%
“…In a study carried out by Chen and collaborators, the presence of several regulatory networks that can be associated with the progression of TAO, such as the NEAT1/miR-1-3p/GNA 12 pathway, was demonstrated, in addition to identifying the involvement of 16 miRNAs (3 downregulated and 13 upregulated) that would also have implications in the pathogenesis of the disease. 16 In 2021, a study was carried out with the aim of exploring the effects of exosomal miRNAs associated with TAO in human vascular smooth muscle cells and the presence of 39 miRNAs was demonstrated compared to controls (10 downregulated and 29 upregulated) with particular importance in miRNA 233-5p since the results of the study suggest that the overexpression of this miRNA generates a suppression of the cell viability of vascular smooth muscle cells and, conversely, the suppression of the miRNA 233-5p was related to greater cell viability. 17 However, other molecules have been identified such as miRNA 100, which has an anti-inflammatory function in chronic inflammation, so the hypothesis of its possible activity in TAO was raised through a study where it was demonstrated that the overexpression of miRNA 100 manages to reduce H2O2 apoptosis and inflammatory damage in human umbilical vein endothelial cells through the inactivation of signaling pathways that mainly involve the Notch pathway, which could be considered a therapeutic target in the future.…”
Section: Micro-rna and Buerger's Diseasementioning
confidence: 99%

Thromboangiitis obliterans: a review

Correa-Posada,
García-Velez,
Hurtado-Mosquera
et al. 2024
Int Surg J